2021
DOI: 10.1101/2021.02.26.433098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a two-stage model of action-stopping: Attentional capture explains motor inhibition during early stop-signal processing

Abstract: The ability to stop an already initiated action is paramount to adaptive behavior. Most scientific debate in the field of human action-stopping currently focuses on two interrelated questions. First: Which mental and neural processes underpin the implementation of inhibitory control, and which reflect the attentional detection of salient stop-signals instead? Second: Why do physiological signatures of inhibition occur at two different latencies after stop-signals (for visual signals, either before or after ~15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Our study also adds more evidence to models involving multiple stages of stopping, such as the pause-then-cancel model (Schmidt and Berke, 2017;Tatz et al, 2021). In the Threshold model beta effectively pauses both decision processes, buying time for the stop process to catch up.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our study also adds more evidence to models involving multiple stages of stopping, such as the pause-then-cancel model (Schmidt and Berke, 2017;Tatz et al, 2021). In the Threshold model beta effectively pauses both decision processes, buying time for the stop process to catch up.…”
Section: Discussionmentioning
confidence: 82%
“…SSRTs were estimated using the integration method (Verbruggen et al, 2019). Using the extracted timing of the beta bursts (see above), we estimated the probability of responding to the Stop cue, P(Respond), as a function of the time relative to the burst.…”
Section: Analyzing Behavior In Relation To Beta Bursts In Stop Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it should be noted that recent work on rodents has suggested that AS might be achieved by the combination of two consecutive neural inhibitory processes: an early one only pausing the action, and a later one potentially cancelling it ( 102 , 103 ). Future work should investigate the hypothesis of a multi-phasic AS process examining humans’ muscular activity, particularly considering the interesting analogies between AS and other RABs ( 104 ). Supramodality .…”
Section: Response Latency and Its Sources Of Variabilitymentioning
confidence: 99%
“…The earlier timing of the prEMG peak latency compared to the SSRT has been replicated in a number of independent studies (Hannah et al, 2020;Jana et al, 2020;Raud et al, 2020aRaud et al, , 2020bTatz et al, 2021;Thunberg et al, 2020). However, while the existence of the prEMG is relatively well-established, its characteristics and utility has not been explored sufficiently to declare it an unambiguous biomarker of the stopping latency.…”
Section: Introductionmentioning
confidence: 96%